Introduction to world literature : an adventure in human experience - Alcantara, Rebecca D.; Cabanilla, Josefina Q.;Casambre, Alejandro J. (Quezon City, Philippines : Katha Publishing Co, Inc., 2000)
This materials presented in this book are the natural outgrowth of the writers' experience with the problem of teaching an introductory course in literature. It meets a real and long felt need for a basic reading text for classroom use.
Section One. The true, the good and the beautiful -- Section Two. Values and ideas -- Section Three. Achievement and Endeavor -- Section Four. The voyage of life: its joys, travails and perplexities.
Keywords: WORLD LITERATURE